The Formal/Informal Employment Earnings GAP: Evidence From Turkey - Aysıt Tansel; Elif Öznur Kan (Turkish Economic Association, 2012)
In this study, we examine the formal/informal sector earnings differentials in the Turkish labor market using detailed econometric methodologies and a novel panel data set drawn from the 2006-2009 Income and Living Conditions Survey (SILC). In particular, we test if there is evidence of traditional segmented labor markets theory which postulates that informal workers are typically subject to lower remuneration than similar workers in the formal sector. Estimation of standard Mincer earnings equations at the mean using OLS on a pooled sample of workers confirms the existence of an informal penalty, but also shows that almost half of this penalty can be explained by observable variables. Along wage/self-employment divide, our results are in line with the traditional theory that formal-salaried workers are paid significantly higher than their informal counterparts. Confirming the heterogeneity within informal employment, we find that self-employed are often subject to lower remuneration compared to those who are salaried. Moreover, using quantile regression estimations, we show that pay differentials are not uniform along the earnings distribution. More specifically, we find that informal penalty decreases with the earnings level, implying a heterogeneous informal sector with upper-tier jobs carrying a significant premium and lower-tier jobs being largely penalized. Finally, fixed effects estimation of the earnings gap depict that unobserved individual fixed effects when combined with controls for observable individual and employment characteristics explain the pay differentials between formal and informal employment entirely, thereby implying that formal/informal segmentation may not be a stylized fact of the Turkish labor market as previously thought.
Keywords: 330; Lohndifferenzierung; Informeller Sektor; Arbeitsmarktsegmentierung; Schätzung; Türkei